Effect of Packaging Materials and Wheat Varieties on Damage to Packaging and Wheat by Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae): Management of Ryzopertha dominica in Packaged Food Stuffs (Biological Sciences - PJSIR, 2023)
We investigated the effect of packaging materials namely polyethylene (PT), polypropylene (PP) and polyvinylchloride (PVC) and three wheat varieties namely Galaxy-13, Aas-11 and Shafaq-06 when packaged in above mentioned packaging on damage to packaging and wheat by Rhyzopertha dominica (Coleoptera: Bostrichidae). After 90 days the maximum numbers of scratches, holes, insect penetrations in packaging and weight loss of packaged wheat was in PT followed by PP and minimum was in PVC. Varieties effect though not significant, showed that these damages were relatively less due to wheat variety Aas-11. Microphotography after 90 days showed maximum mean width of openings in scratch damage in PT followed by PP and minimum in PVC. Although, width of openings in holes was maximum in PVC followed by PP and PT in descending order but both scratches and holes in PT and PP usually contained multiple other accompanying damages along with a major damage per each damage, while in PVC damage mostly was either a single opening or with minor small openings showing more susceptibility of PT and PP compared with PVC. These results show none of the packaging was completely resistant to attack by dominica, while variety Aas-11 was relatively less susceptible than the other two varieties.